Back Cover: Enhanced Electrochemical Sensing with Carbon Nanotubes Modified with Bismuth and Magnetic Nanoparticles in a Lab‐on‐a‐Chip (ChemNanoMat 9/2016). Issue 9 (30th August 2016) - Jothimuthu, Preetha; Hsu, Joe L.; Chen, Robert; Inayathullah, Mohammed; Pothineni, Venkata Raveendra; Jan, Antony; Gurtner, Geoffrey C.; Rajadas, Jayakumar; Nicolls, Mark R.
Abstract : By decorating carbon nanotubes with bismuth and iron oxide nanoparticles, an electrochemical sensor for Fe(II) and Fe(III) has been developed. In addition to measuring the total Fe content with a limit of detection of 0.01 nM, the sensor illustrated on the Back Cover is able to distinguish between the two oxidation states of Fe. More information can be found in the Full Paper by J. Rajadas, M. R. Nicolls et al. onpage 904 in Issue 9, 2016 (DOI:10.1002/cnma.201600174 ).